Between Aromatic and Quinoid Structure: A Symmetrical UV to Vis/NIR Benzothiadiazole Redox Switch. Issue 72 (23rd November 2020) - Rietsch, Philipp; Sobottka, Sebastian; Hoffmann, Katrin; Popov, Alexey A.; Hildebrandt, Pascal; Sarkar, Biprajit; Resch‐Genger, Ute; Eigler, Siegfried
Abstract: Reversibly switching the light absorption of organic molecules by redox processes is of interest for applications in sensors, light harvesting, smart materials, and medical diagnostics. This work presents a symmetrical benzothiadiazole (BTD) derivative with a high fluorescence quantum yield in solution and in the crystalline state and shows by spectroelectrochemical analysis that reversible switching of UV absorption in the neutral state, to broadband Vis/NIR absorption in the 1st oxidized state, to sharp band Vis absorption in the 2nd oxidized state, is possible. For the one‐electron oxidized species, formation of a delocalized radical is confirmed by electron paramagnetic resonance spectroelectrochemistry. Furthermore, our results reveal an increasing quinoidal distortion upon the 1st and 2nd oxidation, which can be used as the leitmotif for the development of BTD based redox switches. Abstract : The quinoidial distortion induced in benzothidiazoles upon oxidation was used in this work to design an absorption redox switch. Using spectroelectrochemical analysis, the absorption, fluorescence and localization of the radical were investigated during the redox processes. The symmetrical benzothiadiazole derivative can thus be used as a UV to Vis/NIR absorption switch or as a fluorescence ON/OFF switch. With deeper understanding of the quinodial distortion, it can furthermore be used as the basis for development of other small organic redox switches.